2009
DOI: 10.1111/j.1365-2923.2008.03244.x
|View full text |Cite
|
Sign up to set email alerts
|

Strategies and interventions for the involvement of real patients in medical education: a systematic review

Abstract: Objectives  There is increasing emphasis on encouraging more active involvement of patients in medical education. This is based on the recognition of patients as ‘experts’ in their own medical conditions and may help to enhance student experiences of real‐world medicine. This systematic review provides a summary of evidence for the role and effectiveness of real patient involvement in medical education. Methods  MEDLINE, EMBASE, ERIC, PsychINFO, Sociological Abstracts and CINAHL were searched from the start of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
178
0
14

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(203 citation statements)
references
References 46 publications
(197 reference statements)
11
178
0
14
Order By: Relevance
“…Gjennom søkene i ovennevnte tidsskrifter fant vi tre systematiske litteraturoversikter (Jha, Quinton, Bekker, & Roberts, 2009;Morgan & Jones, 2009;Towle et al, 2010) og to primaerartikler (Thomas et al, 2015;. Vi vil i det som følger beskrive sentrale poeng fra litteraturoversiktene (hovedsakelig fra Towle et al, 2010).…”
Section: Resultatunclassified
“…Gjennom søkene i ovennevnte tidsskrifter fant vi tre systematiske litteraturoversikter (Jha, Quinton, Bekker, & Roberts, 2009;Morgan & Jones, 2009;Towle et al, 2010) og to primaerartikler (Thomas et al, 2015;. Vi vil i det som følger beskrive sentrale poeng fra litteraturoversiktene (hovedsakelig fra Towle et al, 2010).…”
Section: Resultatunclassified
“…Educational interventions should be integrated into existing training programmes to minimise disruption impact of patient involvement on the patients themselves including empowerment and improvement in patient-doctor communication. Patient narratives involving patients sharing their stories with professionals are widely employed as part of medical training (Repper & Breeze 2007;Jha et al 2009). …”
Section: Practice Pointsmentioning
confidence: 99%
“…There is also little evidence of the feasibility or effectiveness of patientcentred interventions and uncertainty over their acceptability amongst patients and health professionals (Davis et al 2007(Davis et al , 2011Peat et al 2009). In medical education, a systematic review reported patient-led teaching for healthcare professionals to be effective in terms of learner satisfaction and improved performance in key areas such as communication skills (Jha et al 2009). This review also highlighted the positive…”
Section: Introductionmentioning
confidence: 99%
“…Inclusion criteria were based on a literature review of active patient involvement in education (Jha et al, 2009) and the researchers' experiential knowledge. When selecting participants, efforts were made to diversify the team in terms of age, gender, types of impairment, and experiences as service users.…”
Section: Methodsmentioning
confidence: 99%
“…In health and social care, IPE occurs when two or more professions learn with, from, and about each other to improve collaboration and the quality of services (CAIPE, 2002). In recent years, a growing number of IPE initiatives have called upon people receiving services to act as experts in the teaching, evaluation, and development of educational content (Jha et al, 2009;Towle et al, 2010). Inspired by this innovative approach, a team composed of eight people with intellectual, physical, or sensory disabilities, four graduate students, and three researchers or professors pooled their expertise to co-develop an IPE university course.…”
Section: Introductionmentioning
confidence: 99%